Analysis of The Influence of Product Quality and Price on Customer Loyalty Through Customer Satisfaction as An Intervening Variable in Restaurants Hisana Fried Chicken Surabaya - Satrio Sudarso; Susanto Sukiman (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2022)
Every entrepreneur in the culinary field is required to compete competitively in terms of improving product quality and managing price factors to be able to create consumer satisfaction which can affect loyalty. The research location was conducted at one of the Hisana Fried Chicken outlets in the Surabaya area. The criteria for the consumer sample are those who are over 17 years of age and also have at least become Hisana customers, with a minimum of 2 (two) previous purchases in the last 1 (one) month. The number of samples is 100 respondents. The statistical analysis calculation method uses the SPSS program in processing and evaluating the results of the questionnaire to test the quality of the data, while to process and evaluate the results of the path analysis test, hypothesis to evaluate the 'goodness of fit indices' model using the Structural Equation Modeling (SEM) method with the AMOS program. The results of data processing show (1) product quality has a positive and significant effect on consumer satisfaction (2) product quality has a positive and significant effect on consumer loyalty (3) price has a significant negative effect (opposite) on customer satisfaction (4) price has a significant effect negatively (contrary) to consumer loyalty (5) customer satisfaction is positive but does not have a significant effect on customer loyalty.